Positive electrode active material precursor and positive electrode active material for secondary battery
The use of a core-shell structured positive electrode active material precursor with specific metal compositions addresses the structural and performance issues in high nickel content batteries, resulting in improved stability and capacity.
Patent Information
- Application Number
- JP2024146988
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-08-28
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing positive electrode active materials in secondary batteries, particularly those with high nickel content, face issues such as structural instability, cation mixing, and excessive oxygen generation, leading to reduced lifespan and performance.
The development of positive electrode active material precursor particles with a core-shell structure, where the core contains nickel and aluminum with a higher nickel and aluminum content than the shell, which contains cobalt and potentially nickel and manganese, helps to suppress direct contact with the electrolyte, enhance structural stability, and reduce oxygen generation.
This approach results in a positive electrode active material with improved structural integrity, reduced gas generation, and enhanced charge/discharge capacity, leading to increased battery lifespan and performance.
Smart Images

Figure 2025039532000001_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to cathode active material particles and precursor particles thereof contained in a cathode active material of a secondary battery, and more particularly to cathode active material precursor particles and cathode active material particles for a secondary battery including a core portion and a shell portion.
Background Art
[0002] With the development of portable mobile electronic devices such as smartphones, MP3 players, and tablet PCs, the demand for secondary batteries capable of storing electrical energy has increased explosively. In particular, with the emergence of electric vehicles, medium and large-sized energy storage systems, and portable devices that require high energy density, the demand for lithium secondary batteries is increasing.
[0003] As a lithium composite oxide contained in the cathode active material, the substance that has received the most attention in recent years is lithium nickel manganese cobalt oxide Li(Ni x Co y Mn z )O2 (wherein x, y, and z are atomic fractions of independent oxide composition elements, respectively, 0 < x ≦ 1, 0 < y ≦ 1, 0 < z ≦ 1, and 0 < x + y + z ≦ 1). This cathode active material has the advantage of having a higher capacity than LiCoO2, which has been actively studied and used as a cathode active material, and is inexpensive because the Co content is relatively low.
[0004]
[0005] To make up for these shortcomings, the demand for high nickel-based positive electrode active materials, which have a nickel (Ni) content of 60 mol % or more, as positive electrode active materials for secondary batteries, has started to increase.
[0006] However, although such nickel-rich positive electrode active materials have the advantage of high energy density, the increased Ni content causes problems such as increased structural instability due to Li / Ni cation mixing, physical disconnection of internal particles due to microcracks, and deepening electrolyte depletion, resulting in rapid deterioration of life characteristics at room and high temperatures.
[0007] In addition, the high Ni content makes the structure unstable, which increases the reaction with the electrolyte on the surface and interface of the particles, resulting in the release of a large amount of gas during repeated charging and discharging, resulting in reduced life characteristics. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention provides a positive electrode active material precursor and a positive electrode active material that suppress direct contact between the surface and the electrolyte and have a reinforced bulk structure in order to reduce the amount of gas generation, which directly affects the shortening of the lifespan.
[0009] The present invention aims to solve the problem that it is difficult to ensure uniformity in coating and doping due to process characteristics as the production volume of positive electrode active material precursors and positive electrode active materials increases in the industrial field.
[0010] The present invention provides a positive electrode active material precursor and a positive electrode active material capable of suppressing cation mixing, maintaining a layered structure, and suppressing oxygen evolution. [Means for solving the problem]
[0011] A positive electrode active material precursor particle according to one embodiment of the present invention includes a core portion and a shell portion, the core portion includes nickel (Ni) and aluminum (Al), the shell portion includes cobalt (Co), and the nickel (Ni) molar percentage value of the core portion is greater than the nickel (Ni) molar percentage value of the shell portion, the aluminum (Al) molar percentage value of the core portion is greater than the aluminum (Al) molar percentage value of the shell portion, and the cobalt (Co) molar percentage value of the shell portion is greater than the cobalt (Co) molar percentage value of the core portion.
[0012] In one embodiment, the shell portion of the positive electrode active material precursor particle may further include nickel (Ni).
[0013] In one embodiment, the shell portion of the positive electrode active material precursor particle may further include manganese (Mn).
[0014] In one embodiment, the shell portion of the positive electrode active material precursor particle may not contain aluminum (Al).
[0015] In one embodiment, the core portion of the positive electrode active material precursor particle may not contain cobalt (Co).
[0016] In one embodiment, the core portion of the positive electrode active material precursor particle may not contain manganese (Mn).
[0017] In one embodiment, the positive electrode active material precursor particles may contain 0.05 mol % to 0.25 mol % of aluminum (Al) relative to the total transition metals contained in the positive electrode active material precursor particles.
[0018] In one embodiment, the positive electrode active material precursor particle may further include a concentration gradient portion between the core portion and the shell portion, in which one or more transition metals have a concentration gradient.
[0019] A positive electrode active material particle according to one embodiment of the present invention includes a core portion and a shell portion, the core portion includes nickel (Ni) and aluminum (Al), the shell portion includes cobalt (Co), and the nickel (Ni) molar percentage value of the core portion is greater than the nickel (Ni) molar percentage value of the shell portion, the aluminum (Al) molar percentage value of the core portion is greater than the aluminum (Al) molar percentage value of the shell portion, and the cobalt (Co) molar percentage value of the shell portion is greater than the cobalt (Co) molar percentage value of the core portion.
[0020] In one embodiment, the positive electrode active material particles may further include a concentration gradient portion between the core portion and the shell portion, in which one or more transition metals have a concentration gradient.
[0021] In one embodiment, the positive electrode active material particles may further include a coating oxide.
[0022] The positive electrode active material particles according to one embodiment of the present invention can be produced from the positive electrode active material precursor particles.
[0023] In one embodiment, the positive electrode active material particles may further include a coating oxide. A positive electrode according to an embodiment of the present invention may include the positive electrode active material particles. Effect of the Invention
[0024] As an effect, the present invention provides a positive electrode active material precursor and a positive electrode active material that suppress direct contact between the surface and the electrolyte and have a reinforced bulk structure in order to reduce the amount of gas generation that directly affects the shortening of the life span.
[0025] As an effect, the present invention solves a problem in which it is difficult to ensure uniformity in coating and doping due to process characteristics as the production volume of positive electrode active material precursors and positive electrode active materials increases in the industrial sector.
[0026] As an advantage, the present invention provides a positive electrode active material precursor and a positive electrode active material that can suppress cation mixing, maintain a layered structure, and suppress oxygen evolution. [Brief description of the drawings]
[0027] [Figure 1] 3A and 3B are diagrams illustrating cross-sectional SEM images and EDX analysis results for a positive electrode active material precursor particle according to an embodiment of the present invention. [Diagram 2] FIG. 4 is a diagram showing the results of FWHM(104) analysis of positive electrode active material particles according to comparative examples and examples of the present invention. [Diagram 3] FIG. 13 is a diagram showing the results of analyzing high-temperature life characteristics of batteries according to a comparative example and an embodiment of the present invention. [Figure 4] FIG. 13 is a diagram showing the results of an analysis of gas generation rates of batteries according to a comparative example and an example of the present invention. [Diagram 5] FIG. 13 is a diagram showing the results of an analysis of gas generation rates of batteries according to a comparative example and an example of the present invention. [Figure 6] FIG. 4 is a diagram showing the results of FWHM(104) analysis of positive electrode active material particles according to comparative examples and examples of the present invention. [Figure 7] FIG. 4 is a diagram showing the results of an analysis of the charge / discharge capacity of batteries according to a comparative example and an example of the present invention. [Figure 8] FIG. 4 is a diagram showing the results of an analysis of the charge / discharge capacity of batteries according to a comparative example and an example of the present invention. [Figure 9] FIG. 4 is a diagram showing the results of an analysis of charge / discharge capacity efficiency of batteries according to a comparative example and an example of the present invention. [Figure 10] FIG. 13 is a diagram showing the results of an analysis of gas generation rates of batteries according to a comparative example and an example of the present invention. [Figure 11] FIG. 13 is a diagram showing the results of an analysis of gas generation rates of batteries according to a comparative example and an example of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] As used herein, terms such as "comprises" should be understood as open-ended terms that encompass the possibility of including other configurations.
[0029] As used herein, the terms "preferred" and "preferably" refer to embodiments of the invention that may provide certain advantages, under certain circumstances, but are not intended to exclude other embodiments from the scope of the invention.
[0030] Additionally, as used in the specification and the appended claims, the singular forms "a," "an," and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0031] Meanwhile, the technical features described below relate to one aspect for achieving the effects aimed at by the present invention as described above.
[0032] That is, the cathode active material precursor particles and the cathode active material particles according to one embodiment of the present invention include technical features according to one embodiment described below, and thus when applied to a secondary battery, the battery characteristics can be significantly improved.
[0033] The present invention relates to a positive electrode active material particle and a precursor particle thereof contained in a positive electrode active material of a secondary battery, and the type of the secondary battery is not limited as long as the secondary battery is a battery manufactured so that external electric energy can be converted into a form of chemical energy, stored, and reused. As a more preferred example, the present invention may relate to a positive electrode active material particle and a precursor particle thereof contained in a positive electrode active material of a lithium ion secondary battery.
[0034] First, the positive electrode active material precursor particles of the present invention will be described. The positive electrode active material precursor particles according to one embodiment of the present invention may be a material containing nickel (Ni).
[0035] In one embodiment, the positive electrode active material precursor particles may be a nickel hydroxide.
[0036] In one embodiment, the nickel-based hydroxide can be represented by the following Chemical Formula 1: (chemical 1) Ni x Co y M 1-x-y (OH)2
[0037] In the above Chemical Formula 1, M is selected from the group consisting of Zr, Mn, Al, B, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, and 0.5≦x≦1.0, 0.0≦y≦0.4, and 0.0≦1-xy≦0.4.
[0038] In one embodiment, the nickel-based hydroxide can be represented by the following formula 1-1. (Chem.1-1) Ni x’ Co y’ M1 z’ M2 1-x’-y’-z’ (OH)2
[0039] In the above Chemical Formula 1-1, M1 is Al or Mn, and M2 is selected from the group consisting of Zr, B, S, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, where 0.5≦x′≦1.0, 0.0≦y′≦0.4, 0.0≦z′≦0.4, and 0.0≦1-x′-y′-z′≦0.4.
[0040] In one embodiment, in the nickel-based hydroxide, x and / or x', which means nickel (Ni) mole percent relative to the total transition metal mole percent, may be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. In particular, x and / or x' may be 0.8 or more, or 0.9 or more, which is a high nickel-based hydroxide.
[0041] In one embodiment, in the nickel-based hydroxide, y and / or y', which means the mole percent of cobalt (Co) relative to the mole percent of all transition metals, may be 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.
[0042] A positive electrode active material precursor particle according to one embodiment of the present invention includes a core portion and a shell portion.
[0043] In one embodiment, the core portion of the positive electrode active material precursor particle may include nickel (Ni) and aluminum (Al).
[0044] In one embodiment, the nickel (Ni) mol % value of the core portion of the positive electrode active material precursor particle may be greater than the nickel (Ni) mol % value of the shell portion.
[0045] In one embodiment, the aluminum (Al) mol % value of the core portion of the positive electrode active material precursor particle may be greater than the aluminum (Al) mol % value of the shell portion.
[0046] In one embodiment, the shell portion of the positive electrode active material precursor particle may not contain aluminum (Al).
[0047] In one embodiment, the shell portion of the positive electrode active material precursor particle may contain cobalt (Co).
[0048] In one embodiment, the cobalt (Co) mol % value of the shell portion of the positive electrode active material precursor particle may be greater than the cobalt (Co) mol % value of the core portion.
[0049] In one embodiment, the core portion of the positive electrode active material precursor particle may not contain cobalt (Co).
[0050] In one embodiment, the shell portion of the positive electrode active material precursor particle can contain nickel (Ni).
[0051] In one embodiment, the shell portion of the positive electrode active material precursor particle may contain manganese (Mn).
[0052] In one embodiment, the core portion of the positive electrode active material precursor particle may not contain manganese (Mn).
[0053] In the "positive electrode active material precursor particle" of this specification, the specific transition metal molar percentage of the core portion means the specific transition metal molar percentage relative to the total transition metals contained in the core portion, and the specific transition metal molar percentage of the shell portion means the specific transition metal molar percentage relative to the total transition metals contained in the shell portion.
[0054] The positive electrode active material precursor particle of the present invention includes a core portion and a shell portion having different compositions, and is produced by increasing the aluminum (Al) molar concentration of the core portion compared to the shell portion, or by including aluminum (Al) only in the core portion to the exclusion of the shell portion.
[0055] In the past, in order to reduce gas generation, which directly affects the shortening of the life span of a positive electrode active material, a method of strengthening the bulk structure by doping with a specific transition metal element was used. To this end, after preparing a lithium composite oxide, the transition metal element was coated on the surface and sintered to diffuse into the structure, or the transition metal element was added during the sintering step of mixing with a lithium compound and diffused into the structure to be doped. However, as the production volume of a positive electrode active material precursor and a positive electrode active material increases in the industry, there has been a problem in that it is difficult to ensure uniformity in coating and doping due to process characteristics.
[0056] Therefore, in the present invention, in the step of producing a precursor, the core portion is doped with more aluminum (Al) than the shell portion, or aluminum (Al) is doped only in the core portion excluding the shell portion, thereby uniformly doping aluminum (Al) within the core portion.
[0057] The present invention can uniformly dope aluminum (Al) into the core of the positive electrode active material precursor particle, and can be used to manufacture the positive electrode active material particle without using Al. 3+By uniformly disposing the cations in the lithium (Li) layer or transition metal layer, the capacity can be increased by suppressing cation mixing.
[0058] The present invention also relates to Al 3+ By uniformly disposing electrochemically inactive cations such as those mentioned above in the core portion, oxygen generation can be further suppressed.
[0059] In addition, the positive electrode active material precursor particles of the present invention maximize such effects by increasing the molar concentration of cobalt (Co) in the shell portion compared to the core portion, by including cobalt (Co) only in the shell portion excluding the core portion, by increasing the molar concentration of nickel (Ni) in the core portion compared to the shell portion, by increasing the molar concentration of manganese (Mn) in the shell portion compared to the core portion, or by including manganese (Mn) only in the shell portion excluding the core portion.
[0060] In this manner, the present invention controls the composition of the core and shell when preparing the cathode active material precursor particles, and uniformly dopes aluminum (Al) into the core of the precursor particles, thereby improving the battery characteristics when the cathode active material prepared from the core and shell is applied to a battery.
[0061] The aluminum (Al) mol% value relative to the total transition metals contained in the positive electrode active material precursor particles of the present invention is 0.25 mol% or less, 0.2 mol% or less, 0.15 mol% or less, 0.05 mol% or more, 0.06 mol% or more, 0.07 mol% or more, 0.08 mol% or more, or 0.09 mol% or more, more preferably 0.07 mol% to 0.2 mol%, and even more preferably 0.09 mol% to 0.15 mol% to further improve the battery characteristics. When aluminum (Al) is doped at a specific content or more, the movement of Li ions is suppressed due to the pillar effect, so that a decrease in charge / discharge capacity may occur. In addition, when the aluminum (Al) content is too low, the above-mentioned effect may be low. Therefore, when aluminum (Al) is doped at a content within the above range, the structural safety is improved and the charge / discharge capacity can be increased.
[0062] The present invention can strengthen the structure and significantly suppress gas generation during high temperature storage by applying a specific process, applying a specific doping material, and numerically controlling the doping content.
[0063] In the core portion of the positive electrode active material precursor particle of the present invention, the nickel (Ni) molar percentage relative to all transition metals contained in the core portion may be 80 mol % or more, 85 mol % or more, 90 mol % or more, or 95 mol % or more.
[0064] In the shell portion of the positive electrode active material precursor particle of the present invention, the nickel (Ni) molar percentage relative to the total transition metals contained in the shell portion may be 60 mol % or more, 65 mol % or more, 85 mol % or less, 80 mol % or less, or 75 mol % or less.
[0065] In the shell portion of the positive electrode active material precursor particle of the present invention, the molar percentage of cobalt (Co) relative to the total transition metals contained in the shell portion may be 40 mol % or less, 30 mol % or less, 10 mol % or more, or 20 mol % or more.
[0066] In the shell portion of the positive electrode active material precursor particle of the present invention, the manganese (Mn) mol % value relative to the total transition metals contained in the shell portion may be 20 mol % or less, 15 mol % or less, or 10 mol % or less.
[0067] In the present invention, by controlling the core and shell contents of the positive electrode active material precursor particles within the above range, the structure can be strengthened and gas generation during high temperature storage can be significantly suppressed.
[0068] In addition, in the present invention, when aluminum (Al) is mixed at a specific stage of the precursor production process, and then mixed with a lithium compound and subjected to a first heat treatment, the heat treatment is performed at 670°C to 700°C, more preferably 680°C to 690°C, thereby stabilizing the structure and significantly improving the charge / discharge capacity.
[0069] In one embodiment, the average thickness of the core portion of the positive electrode active material precursor particle (the average length from the center of the secondary particle to the surface of the core portion) may be 90% or more, 93% or more, 98% or less, or 97% or less of the radius of the secondary particle.
[0070] In one embodiment, the average thickness of the core portion of the positive electrode active material precursor particle may be 4.5 μm or more, 5.0 μm or more, 5.5 μm or more, and 7.0 μm or less, 6.5 μm or less, or 6.0 μm or less.
[0071] In one embodiment, the average thickness of the shell portion of the positive electrode active material precursor particle (the average length from the surface of the core portion of the secondary particle to the surface of the secondary particle, or the average length from the outer surface of the concentration gradient portion of the secondary particle to the surface of the secondary particle) may be 10% or less, 5% or less, 2% or more, or 3% or more of the radius of the secondary particle.
[0072] In one embodiment, the average thickness of the shell portion of the positive electrode active material precursor particle may be 0.10 μm or more, 0.15 μm or more, 0.20 μm or less, 0.35 μm or less, or 0.30 μm or less.
[0073] Meanwhile, in this specification, "particle diameter" refers to the average diameter (D50) when the particles are spherical, and "particle radius" means 1 / 2 of the above-mentioned "particle diameter".
[0074] In the present invention, the composition ratio of the core portion and the shell portion of the positive electrode active material precursor particle is adjusted while the thickness of the core portion and the shell portion is adjusted to the above range, thereby improving battery characteristics such as structural safety and lifespan.
[0075] In one embodiment, the positive electrode active material precursor particles may have a diameter of 8 μm to 20 μm.
[0076] In one embodiment, the positive electrode active material precursor having the above particle size can be used alone (unimodal) or can be used together with small particles having a smaller particle size (bimodal).
[0077] The positive electrode active material precursor particle of the present invention may further include a concentration gradient portion between the core portion and the shell portion, in which at least one transition metal has a concentration gradient.
[0078] In one embodiment, the average thickness of the concentration gradient portion of the positive electrode active material precursor particle (the average length from the surface of the core portion of the secondary particle to the outer surface of the concentration gradient portion of the secondary particle) may be 10% or less, 5% or less, 2% or more, or 3% or more of the radius of the secondary particle.
[0079] In one embodiment, the average thickness of the concentration gradient portion of the positive electrode active material precursor particle may be 0.10 μm or more, 0.15 μm or more, 0.20 μm or more, 0.35 μm or less, or 0.30 μm or less.
[0080] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of cobalt (Co) increases in a direction from the core portion to the shell portion.
[0081] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of nickel (Ni) decreases in a direction from the core portion to the shell portion.
[0082] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of manganese (Mn) increases in a direction from the core portion to the shell portion.
[0083] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of aluminum (Al) decreases in a direction from the core portion to the shell portion.
[0084] Next, the positive electrode active material particles of the present invention will be described.
[0085] The positive electrode active material particles according to one embodiment of the present invention may be a lithium-nickel based composite oxide containing lithium, nickel, and oxygen.
[0086] In one embodiment, the positive electrode active material particles may contain cobalt.
[0087] In one embodiment, the positive electrode active material particles may contain manganese (Mn) and / or aluminum (Al).
[0088] In one embodiment, the positive electrode active material particles can be represented by Formula 2 below. (chemical 2) Li a Ni x Co y M 1-x-y O2
[0089] In the formula 2, M is selected from the group consisting of Zr, Mn, Al, B, S, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, and 0.9≦a≦1.2, 0.5≦x≦1.0, 0.0≦y≦0.4, and 0.0≦1-xy≦0.4.
[0090] In one embodiment, the positive electrode active material particles can be represented by the following Formula 2-1. (Case 2-1) Li a’ Ni x’ Co y’ M1z’ M2 1-x’-y’-z’ O2
[0091] In the above formula 2-1, M1 is Al or Mn, and M2 is selected from the group consisting of Zr, B, S, Ba, Ce, Cr, F, Mg, V, Ti, Fe, Zn, Si, Y, Nb, Ga, Sn, Mo, W, P, Sr, and combinations thereof, and is within the range of 0.9≦a'≦1.2, 0.5≦x'≦1.0, 0.0≦y'≦0.4, 0.0≦z'≦0.4, and 0.0≦1-x'-y'-z'≦0.4.
[0092] In one embodiment, in the positive electrode active material particles, a and / or a', which means the mol% of lithium (Li) relative to the total mol% of transition metals excluding lithium (Li), may be 0.9 or more, 1.0 or more, 1.2 or less, 1.1 or less, or 1.05 or less.
[0093] In one embodiment, in the positive electrode active material particles, x and / or x', which means nickel (Ni) mole % relative to the total transition metal mole % excluding lithium (Li), may be 0.5 or more, 0.6 or more, 0.7 or more, 0.8 or more, or 0.9 or more. In particular, x and / or x' may be a high nickel-based lithium composite oxide having 0.8 or more, or 0.9 or more.
[0094] In one embodiment, in the positive electrode active material particles, y and / or y′, which means the mole percent of cobalt (Co) relative to the mole percent of all transition metals excluding lithium (Li), may be 0.4 or less, 0.3 or less, 0.2 or less, or 0.1 or less.
[0095] The crystal structure of the positive electrode active material particles according to one embodiment of the present invention may be a hexagonal α-NaFeO2 (R-3m space group).
[0096] A positive electrode active material particle according to one embodiment of the present invention includes a core portion and a shell portion.
[0097] In one embodiment, the core portion of the positive electrode active material particle may include nickel (Ni) and aluminum (Al).
[0098] In one embodiment, the nickel (Ni) mol % value of the core portion of the positive electrode active material particle may be greater than the nickel (Ni) mol % value of the shell portion.
[0099] In one embodiment, the aluminum (Al) mol % value of the core portion of the positive electrode active material particle may be greater than the aluminum (Al) mol % value of the shell portion.
[0100] In one embodiment, the shell portion of the positive electrode active material particle may contain cobalt (Co).
[0101] In one embodiment, the cobalt (Co) mol % value of the shell portion of the positive electrode active material particle may be greater than the cobalt (Co) mol % value of the core portion.
[0102] In one embodiment, the core portion of the positive electrode active material particle may not contain cobalt (Co).
[0103] In one embodiment, the shell portion of the positive electrode active material particle can contain nickel (Ni).
[0104] In one embodiment, the shell portion of the positive electrode active material particle may contain manganese (Mn).
[0105] In one embodiment, the core portion of the positive electrode active material particle may not contain manganese (Mn).
[0106] In the "positive electrode active material particles" of this specification, the mol% value of a specific transition metal in the core portion means the mol% value of the specific transition metal relative to all transition metals excluding lithium (Li) contained in the core portion, and the mol% value of a specific transition metal in the shell portion means the mol% value of the specific transition metal relative to all transition metals excluding lithium (Li) contained in the shell portion.
[0107] The positive electrode active material particles of the present invention include a core portion and a shell portion having different compositions, and can be produced by increasing the aluminum (Al) molar concentration in the core portion compared to the shell portion.
[0108] In addition, in the cathode active material particles of the present invention, the core portion is doped with more aluminum (Al) than the shell portion during the precursor production step, thereby allowing aluminum (Al) to be uniformly doped into the core portion of the cathode active material particles.
[0109] In addition, in the positive electrode active material particles of the present invention, aluminum (Al) is doped in the stage of producing the core portion of the precursor, so that aluminum (Al) is uniformly doped in the core portion of the positive electrode active material particles.
[0110] In addition, the positive electrode active material particles of the present invention maximize these effects by increasing the molar concentration of cobalt (Co) in the shell portion compared to the core portion, by including cobalt (Co) only in the shell portion excluding the core portion, by increasing the molar concentration of nickel (Ni) in the core portion compared to the shell portion, by increasing the molar concentration of manganese (Mn) in the shell portion compared to the core portion, or by including manganese (Mn) only in the shell portion excluding the core portion.
[0111] In one embodiment, the nickel (Ni) molar percentage relative to all transition metals, excluding lithium (Li), contained in the core portion of the positive electrode active material may be 80 mol% or more, 85 mol% or more, 90 mol% or more, or 95 mol% or more.
[0112] In one embodiment, the nickel (Ni) molar percentage relative to all transition metals, excluding lithium (Li), contained in the shell portion of the positive electrode active material may be 60 mol% or more, 65 mol% or more, 85 mol% or less, 80 mol% or less, or 75 mol% or less.
[0113] In one embodiment, the molar percentage of cobalt (Co) in the shell portion of the positive electrode active material relative to all transition metals excluding lithium (Li) contained in the shell portion may be 40 mol% or less, 30 mol% or less, 10 mol% or more, or 20 mol% or more.
[0114] In one embodiment, in the shell portion of the positive electrode active material, the manganese (Mn) mol% value relative to all transition metals excluding lithium (Li) contained in the shell portion may be 20 mol% or less, 15 mol% or less, or 10 mol% or less.
[0115] In the present invention, by controlling the core and shell contents of the positive electrode active material particles within the above range, the structure can be strengthened and gas generation during high temperature storage can be significantly suppressed.
[0116] In one embodiment, the positive electrode active material particles may be secondary particles formed by agglomeration of one or more primary particles.
[0117] In one aspect, the primary particles can include one or more crystallites.
[0118] In one embodiment, the secondary particles of the positive electrode active material may be in a single particle form including one primary particle, and when the primary particle is composed of one crystallite, the secondary particles may be in a single crystal form.
[0119] In another aspect, the positive electrode active material secondary particles may have a multiparticle or polycrystalline form including two or more primary particles, and more preferably have a multiparticle or polycrystalline form including 20 or more primary particles aggregated together.
[0120] In the present invention, the structure can be stabilized and the charge / discharge capacity can be significantly improved by applying a specific process, applying a specific doping material, and numerically controlling the doping content during the preparation of the positive electrode active material particles.
[0121] In one embodiment, the FWHM value means the full width at half maximum (FWHM) value of the (104) peak of XRD defined by a hexagonal lattice having the R-3m space group of the positive electrode active material particles of the present invention. (104) may be in the range of 0.17 or more, 0.18 or more, 0.19 or more, or 0.23 or less, 0.22 or less, 0.21 or less, or 0.20 or less.
[0122] On the other hand, in the present invention, the FWHM (104) is corrected by the following relation 1: (Equation 1) FWHM (104) =FWHM powder(104) -FWHM Si powder(220)
[0123] (In the above-mentioned relational expression 1, FWHM Si powder(220) indicates the full width at half maximum (FWHM) of the (220) peak observed at about 47.3° (2θ) in the XRD measurement of Si powder.
[0124] In the XRD analysis, the full width at half maximum (FWHM) value has deviations and errors due to various variables such as the condition of the analysis equipment, the X-ray source, and the measurement conditions, so it was corrected using the full width at half maximum (FWHM) of Si powder as a standard sample as shown in the above Relation 1.
[0125] In the present invention, the Si powder used was Si powder (product number 215619) from Sigma-Aldrich.
[0126] In the present invention, X-ray diffraction (XRD) analysis was performed using a Bruker D8 Advance diffractometer with Cu Karadiation (1.540598A) at a step size (° / step) of 0.01° / step and a measurement time per step of 0.1 s / step.
[0127] In one embodiment, the average thickness of the core portion of the positive electrode active material particle (the average length from the center of the secondary particle to the surface of the core portion) may be 90% or more, 95% or more, 98% or less, or 97% or less of the radius of the secondary particle.
[0128] In one embodiment, the average thickness of the shell portion of the positive electrode active material particle (the average length from the surface of the core portion of the secondary particle to the surface of the secondary particle, or the average length from the outer surface of the concentration gradient portion of the secondary particle to the surface of the secondary particle) may be 10% or less, 5% or less, 2% or more, or 3% or more of the radius of the secondary particle.
[0129] In the present invention, by adjusting the thicknesses of the core and shell parts in the above ranges while adjusting the compositions of the core and shell parts in the positive electrode active material particles, it is possible to further improve battery characteristics such as structural safety and life.
[0130] In one embodiment, the positive electrode active material particles (secondary particles) may have a diameter of 8 μm to 20 μm.
[0131] In one embodiment, the positive electrode active material particles may further include a concentration gradient portion between the core portion and the shell portion, in which at least one transition metal has a concentration gradient.
[0132] In one embodiment, the average thickness of the concentration gradient portion of the positive electrode active material particle (the average length from the surface of the core portion of the secondary particle to the outer surface of the concentration gradient portion of the secondary particle) may be 10% or less, 5% or less, 2% or more, or 3% or more of the radius of the secondary particle.
[0133] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of cobalt (Co) increases in a direction from the core portion to the shell portion.
[0134] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of nickel (Ni) decreases in a direction from the core portion to the shell portion.
[0135] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of manganese (Mn) increases in a direction from the core portion to the shell portion.
[0136] In one embodiment, the concentration gradient portion may be a concentration gradient portion in which the molar concentration of aluminum (Al) decreases in a direction from the core portion to the shell portion.
[0137] The positive electrode active material particles according to one embodiment of the present invention may be prepared from the positive electrode active material precursor particles, and the characteristics of the positive electrode active material particles are as described above.
[0138] The positive electrode active material particles according to an embodiment of the present invention may further include a coating oxide.
[0139] In one embodiment, the coating oxide may be a coating oxide that occupies at least a portion of the shell portion.
[0140] In one aspect, the coating oxide may occupy at least a portion of at least one of grain boundaries between primary particles, surfaces of the primary particles, and surfaces of secondary particles in the positive electrode active material particles.
[0141] In one embodiment, the coating oxide can be represented by the following Chemical Formula 3: (3) Li p M3 q O r
[0142] In the formula 3, M3 is at least one selected from Ni, Mn, Co, Fe, Cu, Nb, Mo, Ti, Al, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, B, P, S, Eu, Sm, W, Ce, V, Ba, Ta, Sn, Hf, Gd, and Nd; 0≦p≦10, 0 <q≦8、2≦r≦13である。
[0143] For example, in Formula 3, M3 represents a coating element, and the coating oxide may be an oxide of lithium and an element represented by M3 in combination, or an oxide of M3.
[0144] In one example, the coating oxide is Li p Co q O r , Li p W q O r , Li p Zr q O r , Li p Ti q O r , Li p Ni q O r , Li p Al q O r , Li p Mo q O r , Co q O r , Al q O r , W q O r , Zr q O r , Ti q O r , B q O r , Li p (W / Ti) q O r , Li p (W / Zr) q O r , Li p (W / Ti / Zr) q O r , Li p (W / Ti / B)q O r It may be, but is not limited to this.
[0145] The coating oxide may include a concentration gradient portion in which the molar concentration of an element contained in the coating oxide changes. For example, when the coating oxide includes lithium, the molar concentration of lithium may change. Also, for example, the molar concentration of any one or more of M3 contained in the coating oxide may change.
[0146] In one aspect, when the coating oxide occupies at least a portion of a surface region of a primary particle that constitutes an outermost portion of the secondary particle, the concentration gradient portion may decrease, increase, or increase and then decrease from the surface of the primary particle that constitutes the outermost portion of the secondary particle toward the center of the secondary particle.
[0147] In addition, the concentration gradient portion may decrease, increase, or increase and then decrease from a surface of a primary particle that forms the outermost periphery of the secondary particle toward the center of the primary particle.
[0148] In one aspect, when the coating oxide occupies at least a portion of a surface region of a primary particle that does not form the outermost portion of the secondary particle, it may decrease, increase, or increase and then decrease from the surface of the primary particle in a direction toward the center of the primary particle.
[0149] The coating oxide according to an embodiment of the present invention improves the output characteristics of a battery due to its high ionic conductivity, and improves the lifespan of the battery by protecting the surface of the lithium composite oxide. In addition, the coating oxide effectively reduces the residual lithium present on the surface of the lithium composite oxide, thereby preventing side reactions caused by unreacted residual lithium.
[0150] In a more preferred embodiment, the coating oxide may include at least one selected from the group consisting of titanium (Ti), aluminum (Al), zirconium (Zr) and boron (B).
[0151] In one embodiment, when the aluminum (Al) is coated, the aluminum (Al) may be mixed in an amount of 0.5 mol % to 0.7 mol % based on the total transition metals excluding lithium (Li) contained in the positive electrode active material particles, and then heat-treated. When the positive electrode active material particles having the core portion uniformly doped with aluminum (Al) are coated with aluminum (Al) and then heat-treated, the aluminum (Al) is uniformly doped throughout the positive electrode active material particles, thereby further improving the battery characteristics.
[0152] In one embodiment, when the positive electrode active material particles are coated with a combination of 0.5 mol % to 0.7 mol % of aluminum (Al), 0.05 mol % to 0.2 mol % of zirconium (Zr), 0.5 mol % to 0.7 mol % of titanium (Ti), and 0.2 mol % to 0.3 mol % of boron (B) relative to the total transition metals excluding lithium (Li) contained in the positive electrode active material particles, the battery characteristics can be further improved.
[0153] As long as the method for producing a positive electrode active material of the present invention has the above-mentioned technical features, the method is not limited to this method, but as a more preferred embodiment, the positive electrode active material can be produced as follows.
[0154] First, a compound containing aluminum (Al) is mixed with a compound containing a transition metal to produce hydroxides having different compositions for the core and shell.
[0155] Next, the produced hydroxide is mixed with a lithium compound and a first heat treatment is carried out at 670° C. to 690° C. to produce an oxide.
[0156] In a further manufacturing embodiment, the produced oxide can be mixed with a coating oxide and subjected to a second heat treatment at 670°C to 690°C.
[0157] In a further embodiment of the process, the second heat treated oxide can be washed with water and then dried.
[0158] In a further embodiment, the dried oxide can be mixed with additional coating oxide and subjected to a third heat treatment at 250°C to 350°C.
[0159] Meanwhile, the above-mentioned technical features of the positive electrode active material precursor particles may be average technical features of a plurality of positive electrode active material precursor particles contained in the positive electrode active material precursor.
[0160] In addition, the above-mentioned technical features of the positive electrode active material particles may be average technical features of a plurality of positive electrode active material particles contained in the positive electrode active material.
[0161] Meanwhile, the meanings of "≦", "greater than or equal to" and "less than or equal to" described in the present invention can be replaced with the meanings of "<", "more than" and "less than".
[0162] A positive electrode according to an embodiment of the present invention may include the positive electrode active material particles described above.
[0163] Except for the positive electrode active material particles, the positive electrode has a known structure and can be manufactured by a known manufacturing method. The binder, conductive material, and / or solvent are not particularly limited as long as they can be used on the positive electrode current collector of a secondary battery.
[0164] A secondary battery according to an embodiment of the present invention may include the above-described positive electrode active material particles.
[0165] Specifically, the secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and an electrolyte between the positive electrode and the negative electrode, but is not particularly limited thereto as long as it can be used as a secondary battery.
[0166] Examples of the present invention will now be described more specifically.
[0167] Preparation of hydroxide precursor <Example 1> The reactor was charged with 90.8 mol% NiSO4·6H2O relative to the total transition metals contained in the precursor particles, and was stirred while adding 30.1 mol% Al2(SO4), 25 wt.% NaOH, and 28 wt.% NH4OH.
[0168] Next, 2.7 mol% NiSO4·6H2O, 5 mol% CoSO4·7H2O, 1.4 mol% MnSO4·H2O, 25 wt.% NaOH, and 28 wt.% NH4OH were added and stirred relative to the total transition metals contained in the precursor particles to produce particles.
[0169] Here, the temperature inside the reactor was maintained at 58° C., and inert gas N2 was introduced into the reactor to prevent the produced particles from being oxidized.
[0170] After the reaction was completed, washing and dehydration were carried out using a filter press (F / P) equipment.
[0171] Finally, the dehydrated product was dried at 120° C. to produce a hydroxide precursor having a composition of Ni 93.5 mol %, Co 5 mol %, Mn 1.4 mol %, and Al 0.1 mol %.
[0172] <Comparative Example 1> Particles were produced by adding 0.1 mol% Al2(SO4)3, 25 wt.% NaOH, and 28 wt.% NH4OH to an aqueous solution of NiSO4·6H2O:CoSO4·6H2O:MnSO4·H2O mixed in a molar ratio of 94:5:1 in a reactor while stirring.
[0173] The rest of the process was the same as in Example 1, and a hydroxide precursor having a composition of Ni 93.5 mol %, Co 5 mol %, Mn 1.4 mol %, and Al 0.1 mol % was produced.
[0174] <Comparative Example 2> The reactor was charged with 90.9 mol% NiSO4·6H2O relative to the total transition metals contained in the precursor particles, and was stirred while adding 25 wt.% NaOH and 28 wt.% NH4OH.
[0175] Next, 2.7 mol% NiSO4·6H2O, 5 mol% CoSO4·7H2O, 1.4 mol% MnSO4·H2O, 25 wt.% NaOH, and 28 wt.% NH4OH were added and stirred relative to the total transition metals contained in the precursor particles to produce particles.
[0176] The rest of the process was the same as in Example 1, and a hydroxide precursor having a composition of Ni 93.6 mol %, Co 5 mol %, and Mn 1.4 mol % was produced.
[0177] Oxide Production <Example 1-1> The hydroxide precursor prepared in Example 1 was mixed with LiOH (Li / Metal molar ratio=1.04), which is a lithium source material.
[0178] The mixture was placed in a sintering furnace (O2, 670°C, 2°C / min, maintenance time 10 hr), heat-treated, and then cooled in the furnace to produce an oxide.
[0179] <Example 1-2> The only difference from Example 1-1 was that the mixture was heat-treated in a calcination furnace at 680°C instead of in a calcination furnace at 670°C. The other manufacturing methods were the same as those in Example 1-1 to produce an oxide.
[0180] <Example 1-3> The oxide was produced in the same manner as in Example 1-1, except that the mixture was heat-treated in a calcination furnace at 690°C instead of in a calcination furnace at 670°C in Example 1-1.
[0181] <Example 1-4> The only difference from Example 1-1 was that the mixture was heat-treated in a sintering furnace at 700°C instead of 670°C. The other manufacturing methods were the same as those in Example 1-1 to produce an oxide.
[0182] <Example 1-5> The only difference from Example 1 was that the mixture was heat-treated in a calcination furnace at 710°C instead of 670°C. The other manufacturing methods were the same as those in Example 1-1 to produce an oxide.
[0183] <Comparative Example 1-1> The hydroxide precursor prepared in Comparative Example 1 was mixed in place of the hydroxide precursor prepared in Example 1, and the other manufacturing methods were the same as those in Example 1-1 to produce an oxide.
[0184] <Comparative Example 1-2> The only difference from Comparative Example 1-1 was that the mixture was heat-treated in a calcination furnace at 680°C instead of in a calcination furnace at 670°C. The other manufacturing methods were the same as those in Comparative Example 1-1 to produce an oxide.
[0185] <Comparative Example 1-3> The only difference from Comparative Example 1-1 was that the mixture was heat-treated in a calcination furnace at 690°C instead of 670°C. The other manufacturing methods were the same as those in Comparative Example 1-1 to produce an oxide.
[0186] <Comparative Example 1-4> The only difference from Comparative Example 1-1 was that the mixture was heat-treated in a calcination furnace at 700°C instead of 670°C. The other manufacturing methods were the same as those in Comparative Example 1-1 to produce an oxide.
[0187] <Comparative Example 1-5> The only difference from Comparative Example 1-1 was that the mixture was heat-treated in a calcination furnace at 710°C instead of 670°C. The other manufacturing methods were the same as those in Comparative Example 1-1 to produce an oxide.
[0188] <Comparative Example 2-1> The hydroxide precursor prepared in Comparative Example 2 was mixed in place of the hydroxide precursor prepared in Example 1, and the other manufacturing methods were the same as those in Example 1-1 to produce an oxide.
[0189] <Comparative Example 2-2> The only difference from Comparative Example 2-1 was that the mixture was heat-treated in a calcination furnace at 680°C instead of in a calcination furnace at 670°C. The other manufacturing methods were the same as those of Comparative Example 2-1 to produce an oxide.
[0190] <Comparative Example 2-3> The only difference from Comparative Example 2-1 was that the mixture was heat-treated in a calcination furnace at 690°C instead of 670°C. The other manufacturing methods were the same as those of Comparative Example 2-1 to produce an oxide.
[0191] <Comparative Example 2-4> The only difference from Comparative Example 2-1 was that the mixture was heat-treated in a calcination furnace at 700°C instead of 670°C. The other manufacturing methods were the same as those of Comparative Example 2-1 to produce an oxide.
[0192] <Comparative Example 2-5> The only difference from Comparative Example 2-1 was that the mixture was heat-treated in a calcination furnace at 710°C instead of 670°C. The other manufacturing methods were the same as those of Comparative Example 2-1 to produce an oxide.
[0193] Coating oxide production <Example 1-1-1> The oxide prepared in Example 1-1 was mixed with TiO2 0.6mol%, Al2O3 0.6mol%, and ZrO2 0.1mol% in amounts, and then heat-treated in a calciner (O2, 675°C, 4.4°C / min, maintenance time 8hr).
[0194] The heat-treated oxide was divided and crushed, washed with distilled water for 1 hour, and then dried.
[0195] Then, H3BO3 was mixed to a concentration of 0.235% of the dried product weight, and the mixture was placed in a calciner (O2, 300°C, 4.4°C / min, maintenance time 8hr) for heat treatment, and then naturally cooled to produce a coating oxide.
[0196] <Example 1-2-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Example 1-2 was mixed instead of the oxide prepared in Example 1-1.
[0197] <Example 1-3-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Example 1-3 was mixed instead of the oxide prepared in Example 1-1.
[0198] <Example 1-4-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Example 1-4 was mixed instead of the oxide prepared in Example 1-1.
[0199] <Example 1-5-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Example 1-5 was mixed instead of the oxide prepared in Example 1-1.
[0200] <Comparative Example 1-1-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-1 was mixed instead of the oxide prepared in Example 1-1.
[0201] <Comparative Example 1-2-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-2 was mixed instead of the oxide prepared in Example 1-1.
[0202] <Comparative Example 1-3-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-3 was mixed instead of the oxide prepared in Example 1-1.
[0203] <Comparative Example 1-4-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-4 was mixed instead of the oxide prepared in Example 1-1.
[0204] <Comparative Example 1-5-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 1-5 was mixed instead of the oxide prepared in Example 1-1.
[0205] <Comparative Example 2-1-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-1 was mixed instead of the oxide prepared in Example 1-1.
[0206] <Comparative Example 2-2-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-2 was mixed instead of the oxide prepared in Example 1-1.
[0207] <Comparative Example 2-3-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-3 was mixed instead of the oxide prepared in Example 1-1.
[0208] <Comparative Example 2-4-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-4 was mixed instead of the oxide prepared in Example 1-1.
[0209] <Comparative Example 2-5-1> The coating oxide was prepared in the same manner as in Example 1-1-1, except that the oxide prepared in Comparative Example 2-5 was mixed instead of the oxide prepared in Example 1-1.
[0210] Manufacture of lithium secondary batteries A positive electrode slurry was prepared by dispersing 94 wt% of the positive electrode active material prepared in the examples and comparative examples, 3 wt% of artificial graphite, and 3 wt% of PVDF binder in 3.5 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was applied to a 15 μm-thick aluminum (Al) thin film, which is a positive electrode current collector, and dried, and roll pressed to prepare a positive electrode. The loading level of the positive electrode was 7 mg / cm. 2 and the electrode density is 3.2 g / cm 3 It was.
[0211] A lithium foil was used as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) was used as a separator, and a liquid electrolyte containing LiPF6 at a concentration of 1.5 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7 was used to manufacture a coin battery by a commonly known manufacturing process.
[0212] <Experimental Example> (1) Cross-sectional SEM images and EDX analysis A cross-section was obtained by polishing the hydroxide precursor of Example 1 for 1 hour and 30 minutes at a current of 380 μA using a cross-section polisher. A FE-SEM JSM-7610FPlus (JEOL) was used to obtain a cross-sectional SEM image of the hydroxide precursor particles at a voltage of 2 kV, and the concentration change of the transition metal was shown in FIG. 1 by line scanning.
[0213] According to the SEM image in Figure 1, it was confirmed that the core contained Ni and Al, and the shell contained Co and Mn.
[0214] (2) Analysis of FWHM(104) For the positive electrode active materials according to Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-5, the FWHM(104) values according to the first heat treatment temperature were measured and are shown in Figure 2. The method of measuring FWHM(104) was as described above.
[0215] According to the measurement results, in the comparative example in which the composition of the core portion and the shell portion was not changed, the Al doping amount tended to be too small, even though the Al doping amount was the same as that in the examples.
[0216] (3) Analysis of high-temperature life characteristics The lithium secondary batteries according to Examples 1-1-1, 1-2-1, 1-3-1, 1-4-1, and 1-5-1 and Comparative Examples 1-1-1, 1-2-1, 1-3-1, 1-4-1, and 1-5-1 were charged and discharged twice at 25° C., voltage range of 3.0V to 4.3V, and 0.1C / 0.1C, and then charged and discharged once at 45° C., voltage range of 3.0V to 4.4V, and 0.1C / 0.1C. After that, 50 cycles of charge and discharge were performed at 45° C., voltage range of 3.0V to 4.4V, and 1.0C / 1.0C. The ratio of the discharge capacity at the 50th cycle to the initial capacity (cycle capacity retention) was measured and shown in FIG. 6.
[0217] According to the measurement results, it was confirmed that, at the same firing temperature, the same amount of Al was doped in the embodiment, but the high temperature life characteristics were significantly improved compared to the comparative example in which the composition of the core and shell was not changed.
[0218] (4) Analysis of gas generation volume The lithium secondary batteries according to Example 1-1-1 and Comparative Example 1-1-1 were charged to 4.25 V at a constant current of 0.2 C and then stored at 60° C. for up to 80 hours. The volume change of the lithium secondary batteries due to gas generation in the lithium secondary batteries was measured to measure the volume increase rate, which is an index of gas generation, and the results are shown in FIGS. 4 and 5.
[0219] According to the measurement results, based on the full cell evaluation of 300 cycles, in the case of the embodiment, the same amount of Al was doped as in the embodiment, but it was confirmed that the lifetime gas generation rate and the storage gas generation rate were significantly reduced compared to the comparative example in which the composition of the core part and the shell part was not changed.
[0220] (5) Analysis of FWHM(104) For the positive electrode active material particles according to Examples 1-1 to 1-5 and Comparative Examples 2-1 to 2-5, the FWHM(104) values according to the first heat treatment temperature were measured and are shown in Figure 6. The FWHM(104) measurement method was as described above.
[0221] According to the measurement results, it was confirmed that the particle size increased in the embodiment compared to the comparative example of the core-shell structure in which Al was not doped, at the same firing temperature.
[0222] (6) Analysis of charge / discharge capacity and efficiency Charge and discharge experiments were carried out on the lithium secondary batteries according to Examples 1-1-1, 1-2-1, 1-3-1, 1-4-1, and 1-5-1 and Comparative Examples 2-1-1, 2-2-1, 2-3-1, 2-4-1, and 2-5-1 using an electrochemical analyzer (Toyo, Toscat-3100) at 25° C., a voltage range of 3.0 V to 4.25 V, and a discharge rate of 0.2 C. The charge and discharge capacities are shown in FIGS. 7 and 8.
[0223] The charge / discharge efficiency was calculated using the measured charge and discharge capacities and is shown in FIG.
[0224] According to the measurement results, at the same firing temperature, the discharge capacity of the embodiment was significantly improved compared to the comparative example of a core-shell structure not doped with Al, and a significant improvement in charge and discharge efficiency was confirmed.
[0225] (7) Analysis of gas generation volume The lithium secondary batteries according to Example 1-1-1 and Comparative Example 2-1-1 were charged to 4.25 V at a constant current of 0.2 C and then stored at 60° C. for up to 80 hours. The volume change of the lithium secondary batteries due to gas generation in the lithium secondary batteries was measured to measure the volume increase rate, which is an index of gas generation, and the results are shown in FIGS. 10 and 11.
[0226] According to the measurement results, based on the full cell evaluation of 300 cycles, it was confirmed that the lifetime gas generation rate and the storage gas generation rate were significantly reduced in the embodiment compared to the comparative example of the core-shell structure in which Al was not doped.
Claims
1. Contains a core portion and a shell portion, The core portion includes nickel (Ni) and aluminum (Al), The shell portion contains cobalt (Co), the nickel (Ni) mole percent value of the core portion is greater than the nickel (Ni) mole percent value of the shell portion; the aluminum (Al) mole percent value of the core portion is greater than the aluminum (Al) mole percent value of the shell portion; The mole percent value of cobalt (Co) in the shell portion is greater than the mole percent value of cobalt (Co) in the core portion; Here, the mol% value of the specific transition metal in the core portion means the mol% value of the specific transition metal with respect to the total transition metals contained in the core portion, Positive electrode precursor particles, wherein the mol % value of a specific metal in the shell portion means the mol % value of the specific transition metal relative to the total transition metals contained in the shell portion.
2. The positive electrode precursor particle according to claim 1 , wherein the shell portion further comprises nickel (Ni).
3. The positive electrode precursor particle according to claim 1 , wherein the shell portion further contains manganese (Mn).
4. The positive electrode precursor particle according to claim 1 , wherein the shell portion does not contain aluminum (Al).
5. The positive electrode precursor particle of claim 1 , wherein the core portion does not contain at least one selected from the group consisting of cobalt (Co) and manganese (Mn).
6. 2. The positive electrode precursor particles according to claim 1, wherein the positive electrode precursor particles contain 0.05 mol % to 0.25 mol % of aluminum (Al) relative to the total transition metals contained in the positive electrode active material precursor particles.
7. The positive electrode precursor particle according to claim 1 , further comprising a concentration gradient portion between the core portion and the shell portion, in which any one or more transition metals have a concentration gradient.
8. Contains a core portion and a shell portion, The core portion includes nickel (Ni) and aluminum (Al), The shell portion contains cobalt (Co), the nickel (Ni) mole percent value of the core portion is greater than the nickel (Ni) mole percent value of the shell portion; the aluminum (Al) mole percent value of the core portion is greater than the aluminum (Al) mole percent value of the shell portion; The molar percentage of cobalt (Co) in the shell portion is greater than the molar percentage of cobalt (Co) in the core portion; Here, the mol% value of the specific transition metal in the core portion means the mol% value of the specific transition metal with respect to the total transition metals excluding lithium (Li) contained in the core portion, The mol % value of the specific transition metal in the shell portion means the mol % value of the specific transition metal with respect to all transition metals excluding lithium (Li) contained in the shell portion.
9. The positive electrode active material particle according to claim 8 , further comprising a concentration gradient portion between the core portion and the shell portion, in which at least one transition metal has a concentration gradient.
10. The cathode active material particles of claim 8 , further comprising a coating oxide.
11. Positive electrode active material particles produced from the positive electrode active material precursor particles according to claim 1 .
12. 12. The cathode active material particles of claim 11, further comprising a coating oxide.
13. 9. A positive electrode comprising the positive electrode active material particles according to item 8.
Citation Information
Patent Citations
Ternary positive electrode material and preparation method thereof, lithium ion battery and electric vehicle
CN110867576A
Surface-coated lithium ion battery positive electrode material precursor and preparation method thereof
CN113620354A
Lithium-rich nickel-containing ternary composite material as well as preparation method and application thereof
CN115304107A
Nonaqueous electrolyte secondary battery
JP2004127694A
Li-ni composite oxide particle powder for nonaqueous electrolyte secondary battery, its manufacturing method, and nonaqueous electrolyte secondary battery
JP2008251532A